2020
DOI: 10.1186/s12920-020-00797-8
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of molecular links between obesity and cancer through microRNA regulation

Abstract: Background Obesity contributes to high cancer risk in humans and the mechanistic links between these two pathologies are not yet understood. Recent emerging evidence has associated obesity and cancer with metabolic abnormalities and inflammation where microRNA regulation has a strong implication. Methods In this study, we have developed an integrated framework to unravel obesity-cancer linkage from a microRNA regulation perspective. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Moreover, Dogan and colleagues reported 1,558 miR-target gene interactions in obesity, including miR-125b, that were also detected in multiple cancer types. They also showed that metabolism and growth signaling pathways are shared by obesity and obesity-related cancer ( 48 ). Of the pathways reported by Dogan and colleagues, p53-signaling pathway was also identified in our study as a key pathway targeted by the c-miRs of the risk sum score.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Dogan and colleagues reported 1,558 miR-target gene interactions in obesity, including miR-125b, that were also detected in multiple cancer types. They also showed that metabolism and growth signaling pathways are shared by obesity and obesity-related cancer ( 48 ). Of the pathways reported by Dogan and colleagues, p53-signaling pathway was also identified in our study as a key pathway targeted by the c-miRs of the risk sum score.…”
Section: Discussionmentioning
confidence: 99%
“…The existing literature demonstrates that miRNA plays an important role in the occurrence and development of obesity‐related tumors 21 . However, only a few studies have investigated the relationship between changes in the expression level of miRNA and the occurrence and development of EC after obesity.…”
Section: Discussionmentioning
confidence: 99%
“…The existing literature demonstrates that miRNA plays an important role in the occurrence and development of obesity‐related tumors. 21 However, only a few studies have investigated the relationship between changes in the expression level of miRNA and the occurrence and development of EC after obesity. Our previous research has screened an miRNA called miR‐548ag, which is significantly related to the signs of obesity, as well as metabolic and biochemical indicators of the subjects in the population.…”
Section: Discussionmentioning
confidence: 99%
“…Five hypermethylated regions were in genes previously associated with cancer (TRAP1, SLC38A3, CHRM1, EDN2, and PROX1), while six hypomethylated regions were in genes previously associated with cancer (NUMBL, ALDH1B1, FTCD, FASTKD2, FAM96A, and ARHGAP15) [20][21][22][23][24][25][26][27][28][29][30]. Five differentially methylated regions were in genes previously found to be associated with obesity and altered metabolic states (TRAP1, SLC38A3, PROX1, ALDH1B1, and FAM96A) [31][32][33][34][35].…”
Section: Differences In Methylation Patterns Of Hepatocellular Carcin...mentioning
confidence: 92%